A high gain wideband circularly polarized antenna with asymmetric metasurface. Issue 7 (22nd March 2019) - Sheersha, Jils A.; Nasimuddin, N.; Alphones, Arokiaswami
Abstract: An asymmetric‐metasurface based wideband circularly polarized (CP) microstrip antenna using a coaxial probe is proposed for L‐band applications. The antenna involves a stacked asymmetric‐metasurface, a radiating rectangular‐patch and a coaxial feed. An asymmetric‐metasurface is designed using rectangular unit cells and smaller size unit cells along one of the diagonal lines. The asymmetric‐metasurface is placed above a radiating rectangular‐patch with support of foam layer to achieve a wideband CP radiation. The measured performance of the prototype antenna achieves an impedance bandwidth (−10 dB return loss bandwidth) of 15.7% (1.58‐1.85 GHz) with CP bandwidth (3‐dB axial ratio) of 13% (1.58‐1.80 GHz) and gain of ≥9 dBic.